2019
DOI: 10.5123/s1679-49742019000300007
|View full text |Cite
|
Sign up to set email alerts
|

Percepção dos profissionais da Atenção Primária à Saúde como participantes de uma pesquisa nacional sobre HPV: um relato de experiência*

Abstract: Objective: to describe the perception of data collection performed by primary health care professionals as collaborators of the national POP-Brasil survey-Epidemiological Study of National Prevalence of HPV Infection. Methods: in all, 217 professionals from 119 primary care units participated in the POP-Brasil Study conducted in the 26 Brazilian capitals and the Federal District. Results: the professionals were trained and certified locally for collecting data and biological material from 8,580 participants; p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Training of the health team on information and clarification about the vaccine and its benefits could have a relevant impact on the Brazilian National Health System [ 31 ]. Awareness about sexually transmitted infections in primary health care is fundamental, reinforcing the recommendation for vaccination in the right age range [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Training of the health team on information and clarification about the vaccine and its benefits could have a relevant impact on the Brazilian National Health System [ 31 ]. Awareness about sexually transmitted infections in primary health care is fundamental, reinforcing the recommendation for vaccination in the right age range [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, when the project for this study was developed, there was no validated questionnaire for this purpose. In 2018, a comprehensive study with validation of a questionnaire was found; however, this questionnaire was aimed at adolescents and young people aged 16 to 25 years [ 32 , 35 ]. It should also be noted that as the economy of the municipality is based on agriculture, the immigration rate rises during the harvest season, which explains the percentage of people (22.4%; n = 91) who no longer resided in the municipality.…”
Section: Discussionmentioning
confidence: 99%